2011
DOI: 10.1002/jmor.10931
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphology of the gonadal structure related to reproductive strategies in six species of neotropical catfishes (Teleostei: Siluriformes)

Abstract: We studied the relationship between the morphology of the reproductive system and the reproductive strategies of six neotropical catfishes using macroscopic and microscopic analyses. The reproductive system of the examined Siluriformes showed diversified characteristics, but permitted their being grouped according to three reproductive strategies: pelagic spawning, demersal spawning, and internally fertilizing. The pelagic spawners Pseudoplatystoma corruscans and Conorhynchos conirostris have testes that are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 38 publications
4
38
0
2
Order By: Relevance
“…The yellowish colour of the ovaries and the histological features of the follicular cells and zona pellucida of the vitellogenic oocytes are similar to what has been reported by Melo et al (2011). The funnel-shaped micropyle observed in P. maculatus in this study seems to be a common pattern for fish of the Pimelodidae family (Rizzo et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The yellowish colour of the ovaries and the histological features of the follicular cells and zona pellucida of the vitellogenic oocytes are similar to what has been reported by Melo et al (2011). The funnel-shaped micropyle observed in P. maculatus in this study seems to be a common pattern for fish of the Pimelodidae family (Rizzo et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, anastomosis of the seminiferous tubules, a characteristic of testes of the anastomotic tubular type as described by Parenti & Grier (2004), was observed. In the caudal portion of the spent testes of P. maculatus, globular acidophilic secretion was observed, as has also been observed by Melo et al (2011). Some studies showed that this secretion may be related to sperm maturation and nutrition and may play a crucial role in fertilisation (Mazzoldi et al, 2005;Chowdhury & Joy, 2007).…”
Section: Discussionsupporting
confidence: 65%
“…Burgess (1989) identified that the actual fertilization takes place only at the time of the egg deposition, without any males assistance, by using a storage of sperm (Melo et al, 2011), which the females could retain for up to four months (varying upon the species). Hence, the more accurate term ''internal insemination'' had been used recently instead ''internal fertilization'' (Burns et al, 2002;Mazzoldi et al, 2007;Parreira et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Native. Internal fertilisation (Downing Meisner et al 2000, Costa Melo et al 2011, eggs hidden but with no additional parental care (Bailly et al 2008). Carnivore.…”
Section: Trachelyopterus Galeatus (Linnaeus 1766) [Grouper Catfish]mentioning
confidence: 99%